103k views
5 votes
3x
+
9y = -9
x + y = 1

User Icarumbas
by
4.3k points

2 Answers

2 votes

Answer:

Here

the given equations are:-

3x + 9y = -9

or,3(x +3y)= -9

or,x+ 3y = -3 ................. (1)

x + y = 1 ................... (2)

Now , subtracting equation (2) from (1) , we ger:-

x + 3y = -3

x + y = 1

- - -

__________

0 + 2y = -2

or, y = -1

putting value of y in equation (2) , we get:-

x +(-2) = 1

or, x - 2 = 1

or x = 3

HENCE,

x = 3 and y = -1 are the values of x and y .

Thank me later.

User Richard Banks
by
4.9k points
4 votes

Answer:

x=3, y= -2

Explanation:

3x + 9y = -9

x + y = 1

Multiply the second equation by -3

-3x-3y = -3

Add this to the first equation to get rid of the x's

3x + 9y = -9

-3x -3 y = -3

------------------------

6y = -12

Divide by 6

6y/6 = -12/-6

y = -2

3x + 9y = -9

x + y = 1

Multiply the second equation by -9

-9x-9y = -9

Add this to the first equation to get rid of the y's

3x + 9y = -9

-9x -9 y = -9

------------------------

-6x = -18

Divide by -6

-6x/-6 = -18/-6

x = 3

User Tom Redfern
by
5.5k points